PEMANGGILAN NOTARIS DALAM RANGKA PENEGAKAN HUKUM PASKA PERUBAHAN UNDANG-UNDANG JABATAN NOTARIS - Arliman S, Laurensius (Justitia et Pax, 2016)
AbstractNotary is a public official who is authorized to make an authentic act. Law No. 2 of 2014 on the Amendment of Law No. 30 Year 2004 on Notary, explains that, to take a photocopy of a Notary deed minuta and call a Notary in law enforcement, no longer through the Regional Supervisory Council permission. So the question arises, how the basic formation of the Honorary Council of Notaries in Act No. 2 of 2014, and how to call the Notary deed made. Based on research outputs by the author, Honorary Council of Notaries of birth, due to the need of legal protection against a Notary in deed. Notary Honorary Council is indispensable in the implementation of the law enforcement process, where the calling Notary by law enforcement (police, prosecutors, judges) must obtain permission from the Notary Honorary Council. To fill the legal vacuum, because the Honorary Council of Notaries has not been established, the Notary can use the right Dissenters, Indonesian Notary Association urged the government to establish a Notary Honorary Council Implementing Regulation.Keywords: Notary Public; Law Enforcement; Law Notary.IntisariNotaris merupakan seorang Pejabat Publik yang berwenang untuk membuat sebuah akta otentik.Undang Undang Nomor 2 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 30 Tahun 2004 Tentang Jabatan Notaris, menjelaskan bahwa, untuk mengambil fotokopi minuta akta seorang Notaris dan memanggil seorangNotaris dalam penegakan hukum, tidak lagi melalui izin Majelis Pengawas Daerah. Maka timbul pertanyaan, bagaimana dasar pembentukan Majelis Kehormatan Notaris dalam Undang-Undang Nomor 2 Tahun 2014, dan bagaimana memanggil Notaris yang membuatkan akta, Paska Perubahan Undang-Undang Jabatan Notaris Nomor 30 Tahun 2004. Berdasarkan hasil penelitian yang penulis lakukan, Majelis Kehormatan Notaris lahir, akibat kebutuhan perlindungan hukum terhadap seorang Notaris dalam pembuatan akta. Majelis Kehormatan Notaris sangat diperlukan didalam pelaksanaan proses penegakan hukum, dimana pemanggilan Notaris oleh para penegak hukum (polisi, jaksa, hakim) harus mendapat izin dari Majelis Kehormatan Notaris. Untuk mengisi kekosongan hukum, karena Majelis Kehormatan Notaris belum terbentuk, maka Notaris bisa menggunakan hak Ingkar, Ikatan Notaris Indonesia mendesak pemerintah untuk membentuk Peraturan Pelaksana Majelis Kehormatan Notaris.Kata Kunci: Notaris,penegakan hukum, Undang-Undang.